The entrepreneur and the exercise of power in institutional perspective (Dimensión Empresarial, 2016)
n order to achieve a better understanding of the potential development of the field of entrepreneurship, this paper aims to show the need to seek different perspectives to present the idea of a better way to demonstrate the relationship between the entrepreneur and the exercise of power. Our contribution from a different perspective is from the theoretical review of recent and relative area of knowledge, and that starts from understanding the nature of the entrepreneurial individual, and in this sense, make an approximation of the elements that might affect their understanding and analysis, from the developments covered by the practices of power, for which the authors propose as a relevant insight into the nature of the theoretical construction of the project framework
Keywords: Entrepreneur; entrepreneurship; institutional environment; organized power